Beyond Curriculum Standardization: Reconstructing Context-Based Islamic Education Across Schools, Madrasahs, and Pesantrens in Indonesia - Ike Herdiawan; Muslihudin; Abdul Aziz (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study reconstructs Islamic Religious Education beyond curriculum standardization by proposing a context-based framework applicable across schools, madrasahs, and pesantrens in Indonesia. It responds to the need for Islamic education to address socio-cultural diversity, technological transformation, local needs, and contemporary educational challenges while maintaining its Islamic foundations. Using a qualitative library research design, the study employed a critical-integrative review approach. Data were collected from 72 selected publications indexed in Scopus and other reputable academic databases and analyzed through thematic, comparative, and critical synthesis techniques. The findings indicate that curriculum contextualization functions as a transformative paradigm rather than merely a pedagogical strategy. Schools emphasize differentiated instruction and project-based learning, madrasahs integrate national and religious curricula while promoting religious moderation, and pesantrens adopt selective modernization while preserving Islamic traditions. Across these institutions, contextualization enhances curriculum relevance, learner engagement, digital adaptability, and character development. The study's novelty lies in the Context-Based Islamic Education Curriculum (CBIEC) framework, which integrates Islamic foundations, contextual realities, adaptive pedagogies, and future-oriented competencies. The study contributes to curriculum theory by demonstrating how contextualization can reconcile religious authenticity, institutional diversity, and contemporary educational demands.